Analysis of The Benefits of Cash Direct Assistance on Economic Growth in Kedumulyo Village - Kinasih, Dwi Sri; Susilo, Agus (Universitas Muhammadiyah Surakarta, 2022)
This study aims to determine the benefits felt by MSME actors from the results of providing MSME cash direct assistance and to determine the extent to which the results of economic growth in Kedumulyo Village are a result of the provision of direct cash. Data collection techniques in this study using observation, interviews, and documentation. Sources of data in the form of sources, events and activities, as well as documents. The data analysis technique used interactive analysis. The validity of the data is done by using source triangulation and technique triangulation. The results showed that related to the form of distribution of MSME BLT, namely through the nearest BRI Bank, MSME actors received MSME cash assistance 1 time, which was Rp. 2.400.000 million which was used to increase business capital. business development of MSME actors in Kedumulyo Village. Based on the results of the study, it can be concluded that the provision of direct cash assistance to MSMEs can have an impact on economic growth in Kedumulyo Village.